Information Systems: development, research, applications, education : 9th SIGSAND/PLAIS EuroSymposium 2016, Gdansk, Poland, September 29, 2016 : proceedings /: 9th SIGSAND/PLAIS EuroSymposium 2016, Gdansk, Poland, September 29, 2016 : proceedings. ([2016]) - Unknown
No abstract available